(untitled) (Revista de Ensino em Artes, Moda e Design, 2021)
The research studies the fashion editorial as a photographic narrative and analyzes the concepts of relational art, comparing in time the positioning and creative freedom of fashion editorials with their collaborators. More and more art has been building a field that values ​​the image as the place of experiences, in which the viewer is invited to be a participant in the work and to assume the same importance as the artist. The work is only complete with the fruit of this relationship. The authors studied are Nicolas Bourriaud, Anne Cauquelin and Vilém Flusser. Descriptive research is used with a focus on fashion editorials, where the relationship between editorials, employees and their viewers is observed. Finally, we seek to understand how a fashion editorial, the result of a dialogue between inspiration and shared relationships during the artistic process, can be considered a relational form.